PENGARUH PERTUMBUHAN EKONOMI KABUPATEN/KOTA TERHADAP KEMISKINAN KABUPATEN/KOTA DI KALIMANTAN BARAT - B01108112, Deffrinica (Jurnal Curvanomic, 2012)
The reserch aims analyze the influence of regency/municipality economic growh toward regency/municipality poverty in Kalimantan Barat. In this research, the writes employs descriptive menthod to observe independent variabel (economic growh) toward dependend variabel (poverty) which then analyzed namely t test and determination coeficient in order to reach a conclusion that economic growth influence toward poverty. Constanta (C) value which is 3.76 means that the level of poverty in Kalimantan Barat is 3.76, it is assumed the factors which influence the poverty level, economic development (X), is constant. Economic development (X) influence toward level of poverty (Y) can be found by observing the value of regression coefficient of economic development (Y), which is 0.11476%. The result shows that there is a positive correlation between economic development and the level of poverty in Kalimantan Barat. For example, in the Melawi regency, if economic development value is constant, then the level of poverty is increasing as much 1.50%. If the economic development value increases as much 0.50%. The incresing of economic development but is unable to overcome the problem of the poverty level is caused by imbalance between the income of a region and the development in the sectors which are not participate in the effort of overcoming the poverty. Keywords: ECONOMIC GROWTH, POVERTY.